THE EMERGENCE OF DEWAN SYARIAH KOTA SURAKARTA: A Precondition - Yusuf Rohmat Yanuri; Wildan Rahmat Hidayat (Journal of Contemporary Islam and Muslim Societies)
Abstract: This study analyses the social, intellectual, and political history of Dewan Syariah Kota Surakarta (DSKS, The Surakarta Sharia Council), the group that is a forum for many smaller Islamist groups in Solo. This group claimed to unite Muslims in Solo, Central Java. Formed in 2013, this group suddenly organized many mass rallies with negative campaigns and radical notions. This study investigates the factors that contributed to the emergence of the DSKS by integrating both theoretical and empirical approaches. The data for these investigations are gathered through a literature review and on-site research. The literature review is complemented by examining documents and media, especially online sources. One of the most significant is the materials published by DSKS, encompassing website articles, pamphlets, and content on social media platforms. Many factors contributed to the emergence. First, many Islamist figures in Solo such as Abu Bakar Baasyir, Muinudinillah Basri, Tengku Azhar, and Syihabuddin Abdul Muiz. Second, the role and support of Majelis Ulama Indonesia (MUI). Third, the existence of various Salafi movements. Last, Solo is a city that is closely linked to terrorist activities. This study makes an important contribution to the literature on social movements, particularly in the context of Islamic movements in Indonesia. It can serve as a basis for further studies on similar movements in other regions. Keywords: DSKS, Solo, Islamist Groups